2014
DOI: 10.1016/j.enbuild.2014.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Passive energy management through increased thermal capacitance

Abstract: Energy usage within the world is increasing at a drastic rate. Buildings currently consume a major amount of the total energy used within the United States, and most of this energy usage supports heating and cooling. This demand shows that new passive energy management systems are needed. The use of Increased Thermal Capacitance (ITC) is proposed as a new passive energy management system. To increase thermal capacitance, a piping system is either added into a building's walls or ceiling. In this paper, a build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…This thermal storage system saves energy for the entire system by taking advantage of the climate. Using the properties of copper piping found in [3] and the building envelope properties found in [4], it was found that the envelope resistance is 200 times greater than the resistance of the copper pipe; therefore, the copper piping's contribution to the net resistance will be omitted in this first order analysis.…”
Section: Increased Thermal Capacitance With Thermal Storage Managemenmentioning
confidence: 99%
See 4 more Smart Citations
“…This thermal storage system saves energy for the entire system by taking advantage of the climate. Using the properties of copper piping found in [3] and the building envelope properties found in [4], it was found that the envelope resistance is 200 times greater than the resistance of the copper pipe; therefore, the copper piping's contribution to the net resistance will be omitted in this first order analysis.…”
Section: Increased Thermal Capacitance With Thermal Storage Managemenmentioning
confidence: 99%
“…However, the energy savings due to their ITC methodology were rather modest, not taking full advantage of the weather conditions. In order to improve on the work of Carpenter et al [3], a more advanced thermal management system (TSM) is proposed in this paper. The proposed ITC/TSM discussed in this paper takes advantage of daily maximum or minimum ambient temperatures to control the temperature of the water used in the ITC.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations